Alexitimia e depressão : a influência mediadora da autocompaixão e mindfulness - Luiz, Cynthia Borges (2024)
Alexithymia is characterized by difficulty in identifying and describing emotions, while depression manifests as persistent feelings of sadness and apathy. In this context, mindfulness and self-compassion emerge as psychological processes that can moderate the impact of alexithymia on depression, favoring emotional regulation. The present study aimed to investigate the relationship between alexithymia and depression, exploring the mediating role of mindfulness facets and self-compassion factors. To this end, a cross-sectional observational method was used with 145 university students, who responded to a sociodemographic questionnaire and four validated scales in Portuguese: the Five Facet Mindfulness Questionnaire, the Self-Compassion Scale, the Toronto Alexithymia Scale, and the Depression, Anxiety, and Stress Scale. The average age of participants was 25 years, predominantly female and residing in João Pessoa. Mediation analyses revealed that both mindfulness and self-compassion played significant mediating roles in the relationship between alexithymia and depression. Specifically, in the mindfulness model, the facets "Acting with Awareness" and "Non-Judging" were identified as crucial mediators in reducing depressive symptoms. In contrast, in the self-compassion model, the factors "Over-Identification" and "Isolation" emerged as risks, associated with increased depressive symptoms. These findings suggest that interventions focused on developing mindfulness and self-compassion may be effective in emotional regulation and in the treatment of depression in individuals with alexithymia.